2022
DOI: 10.3389/fmed.2022.1026521
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of CD6 as a therapeutic target in cancer and autoimmune disease

Abstract: Autoimmune disease involves loss of tolerance to self-antigen, while progression of cancer reflects insufficient recognition and response of the immune system to malignant cells. Patients with immune compromised conditions tend to be more susceptible to cancer development. On the other hand, cancer treatments, especially checkpoint inhibitor therapies, can induce severe autoimmune syndromes. There is recent evidence that autoimmunity and cancer share molecular targets and pathways that may be dysregulated in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…We demonstrated that UMCD6 increases survival and augments killing by both PBMC and isolated NK cells of both triple-negative breast cancer and prostate cancer cells xenografted into immunodeficient mice. Of particular interest from both cancer immunotherapy and autoimmunity perspectives is the demonstrated ability of UMCD6 to prevent or reverse multiple models of human autoimmune disease [ 10 ], which provides an important advantage compared to current checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that UMCD6 increases survival and augments killing by both PBMC and isolated NK cells of both triple-negative breast cancer and prostate cancer cells xenografted into immunodeficient mice. Of particular interest from both cancer immunotherapy and autoimmunity perspectives is the demonstrated ability of UMCD6 to prevent or reverse multiple models of human autoimmune disease [ 10 ], which provides an important advantage compared to current checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these results provide mechanistic support for anti-CD6 therapy as a promising mAb for cancer immunotherapy. Moreover, because UMCD6 can suppress many autoimmune syndromes by its direct effects on CD4 + T cells [ 3 5 , 10 ], the use of this antibody to treat human cancer could avoid the troubling autoimmune complications frequently seen with current checkpoint inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…As for CD318/CDCP1 (also known as TRASK, SIMA135, or gp140), this CD6 ligand is expressed by fibroblasts and epithelial cells with which T cells interact but not by immune cells [45]. CD318 (CDCP1) is found overexpressed by epithelial and myeloid cancer cells, where it correlates with cancer progression and metastasis initiation [49]. Very recently, biochemical and biophysical evidence support the interaction of CD6 with CD44 [43], a broad tissue distribution and multifunctional cell adhesion receptor mainly involved in hyaluronic acid recognition, the major extracellular matrix component.…”
Section: The Cd6 Receptor: Structure Function Tissue Distribution And...mentioning
confidence: 99%
“…Altogether, these results provide mechanistic support for anti-CD6 therapy as a promising mAb for cancer immunotherapy. Moreover, because UMCD6 can suppress many autoimmune syndromes by its direct effects on CD4 + T cells [3][4][5]10 , the use of this antibody to treat human cancer could avoid the troubling autoimmune complications frequently seen with current checkpoint inhibitors.…”
Section: Introductionmentioning
confidence: 99%